Status of herpetofauna in Rupandehi and Arghakhanchi districts, Nepal - Nepali, Pit Bahadur; Singh, Nanda Bahadur (Journal of Natural History Museum, 2018)
Herpetofauna are unique creature which comprise both amphibians and reptiles. The present study was carried out on herpetofaunal diversity in Rupandehi and Arghakhanchi districts. Each of six sampling stations was conducted in the study areas. Ten standardized 10 x 200 m strip transects and 20-25 standard Quadrat sizes of 20 m x 20 m were set in each station. Observed museum specimens and questionnaire survey were also conducted during data collection. A total of 45 spe cies of herpetofauna was recorded with 9 species of amphibians) and 36 species of reptiles. Six species were from the family Ranidae, two species from Bufonidae and one speciesfrom Rhacophoridae. Lizards were represented by 11 species belonging to four different families. Each of Gekkonidae, Agamidae and Scincidae family was represented by 3 species and the Varanidae by two species. The family Crocodylidae was represented by one species. The order Testudines (turtles) was represented by 2 species from family trionychidae and bataguridae. Twenty two species of snakes were recorded from 6 different families. The amphibian species, namely; Euphlyctis cyanophlyctis, Zakerana nepalensis, Bufo melanostictus and B. stomaticusand reptile species Calotes versicolor were relatively abundant. Seven species of amphibians and18 species of reptiles were common in both districts. The study areas were diverse microhabitats due to the elevation from 71 m to 2004 m with plain, Churia and mountain range.